Electroosmotic control of width and position of liquid streams in hydrodynamic focusing - Li, Haiwang (2012)
This paper presents theoretical and experimental investigations on electroosmotic control of stream width in hydrodynamic focusing. In the experiments, three liquids (aqueous NaCl, aqueous glycerol and aqueous NaCl) are introduced by syringe pumps to flow side by side in a straight rectangular microchannel. External electric fields are applied on the two aqueous NaCl streams. Under the same inlet volumetric flow rates, the applied electric fields are varied to control the interface positions and consequently the width of the focused aqueous glycerol stream. The electroosmotic effect on the width of the aqueous glycerol is measured using fluorescence imaging technique. The electroosmotic effect under different flow rates, different viscosity, and aspect ratio are investigated. The results indicate that the electroosmotic effect on the pressure-driven flow becomes weaker with the increase in flow rates, viscosity ratio or aspect ratio of the channel. The measured results of the focused width of the non-conducting fluid agree well with the analytical model.